Autophagy inhibition due to thymidine analogues as novel mechanism leading to hepatocyte dysfunction and lipid accumulation - Stankov, Metodi Vasilev; Panayotova Dimitrova, Diana; Leverkus, Martin (AIDS <London>, 2012)
Objectives: Prolonged nucleoside reverse transcriptase inhibitors (NRTI) exposure can lead to microvesicular steatosis. We hypothesized that thymidine analogues might interfere with autophagy in hepatocytes, a lysosomal degradation pathway implicated in cell survival and regulation of hepatocyte lipid metabolism. Design: Using HepG2 and HUH7 cell lines and primary human hepatocytes, we performed a comprehensive analysis of NRTI-mediated effects on autophagy. Methods: The impact of zidovudine (ZDV), stavudine (d4T) and lamivudine (3TC) on constitutive and induced autophagy was analyzed by fluorescent and electron microscopy, western blotting and flow cytometry. Effects on hepatocyte autophagy were correlated to cellular viability, mitochondrial dysfunction and intracellular lipid accumulation. Results: ZDV and d4T, but not 3TC, significantly inhibited both constitutive as well as stimulated autophagic activity in a dose-dependent and time-dependent manner. Inhibition of autophagy at therapeutic drug concentrations led to accumulation of dysfunctional mitochondria, increased ROS production, increased apoptosis, decreased proliferation and increased intracellular lipid accumulation. These NRTI effects could be readily resembled by pharmacological and genetic inhibition of hepatocyte autophagy. Conclusion: Our data suggest that thymidine analogues inhibit autophagy in hepatocytes, which in turn leads to increased ROS production, lipid accumulation and hepatic dysfunction. This novel mechanism could contribute to nonalcoholic fatty liver disease in HIV-infected patients.
Gesehen am 17.08.2018